Pemanfaatan Teknologi di Kelurahan Kubu Gadang Kota Payakumbuh sebagai Sarana Informasi, Peningkatan Sumber Daya Manusia, dan Pertumbuhan Ekonomi bagi Pelaku Usaha Mikro Kecil Menegah (UMKM) - Irohito Nozomi; Cendra Wadisman (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2019)
In the current 4.0 era, which is happening in the current technology, it can be said to have almost reached a satisfactory level. Where these developments are very influential in all fields, as now information technology has also been applied in various aspects ranging from human resource development and the development of micro small and medium enterprises (MSMEs). All levels are provided with the ease of existing progress. However, the use of information technology has not been felt in all regions, resulting in gaps in human resources in each region and hampering the rate of economic growth, especially in the micro small and medium business sector. For this reason, it is necessary to have equal distribution of information technology utilization so that it can improve HR and encourage the growth of MSMEs. The purpose of this study is that the use of information technology can improve human resources and strengthen the economy of the community from the MSME sector, especially in Kubu Gadang Urban Village, Payakumbuh. Keywords: Information Technology, Human Resources, SMEs.